Growth rates in modern speleothems from Santana Cave, Brazil, by the Pb-210-method - Bonotto, Daniel Marcos [UNESP]; Karmann, I. [UNESP]; Baskaran, M. M. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
The Santana Cave is located at the Upper Ribeira Touristic State Park (PETAR-Parque Estadual Turistico do Alto Ribeira) in southern São Paulo State, Brazil. This paper describes Pb-210 activity concentration data in soda straw stalactites samples collected at Salao das Flores in Santana Cave that is a fossil tributary of the cave river. Non-expensive alpha counting following some analytical steps for extracting and depositing Pb-210 were used for providing the Pb-210 data. In the analyzed samples, Pb-210 values of increasingly older samples fitted an exponential curve, thus suggesting that the production of Pb-210 has been constant with time. Also, the near-ideal fit indicated that the growth was uniform and there was no break in the continuous growth. The soda straw growth rates were determined from the best fit to the exponential curve through the Pb-210 activity concentration. The results of the measurements allowed estimate a longitudinal rate corresponding to 1.3 mm/yr and a lateral rate of 0.01 mm/yr, which permitted calculate times of 70 years and 317-498 years for their formation, respectively. The lateral growth rate is compatible with values from studies of chemical weathering rates held under laboratory and natural conditions. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Pb-210 dating; Modern speleothems; Santana Cave; Karstic system; Growth rates